Generating human-computer micro-task workflows from domain ontologies - Luz, Nuno (2014)
With the growing popularity of micro-task crowdsourcing platforms, a renewed interest in the resolution of complex tasks that require the coopera-tion of human and machine participants has emerged. This interest has led to workflow approaches that present new challenges at different dimensions of the human-machine computation process, namely in micro-task specification and human-computer interaction due to the unstructured nature of micro-tasks in terms of domain representation. In this sense, a semi-automatic generation envi-ronment for human-computer micro-task workflows from domain ontologies is proposed. The structure and semantics of the domain ontology provides a com-mon ground for understanding and enhances human-computer cooperation.